2017
DOI: 10.1038/bjc.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase-targeting drugs-associated heart failure

Abstract: Background:The impact of cancer therapies on cardiac disease in the general adult cancer survivor population is largely unknown. Our objective was to evaluate which tyrosine kinase-targeting drugs are associated with greater risk for new-onset heart failure (HF).Methods:A nested case–control analysis was conducted within a cohort of 27 992 patients of Clalit Health Services, newly treated with a tyrosine kinase-targeting, and/or chemotherapeutic drug, for a malignant disease, between 1 January 2005 and 31 Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…New targeting strategies of ERK1/2 signaling are of major therapeutic interest, since permanent activation and inactivation of this cascade both appear detrimental. Novel ERK1/2 targeting strategies should increase the therapeutic efficacy by circumventing drug-resistance and reduce cardiac side-effects that currently limit their application 2,4,[56][57][58] . In this regard, interference with ERK dimerization holds promise, since AKT activation as one compensatory mechanism that contributes to drugresistance was prevented in HT29 cells, and most importantly no side-effects were detectable in the AAV9-EDI model nor for the overexpression of monomeric ERK2 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…New targeting strategies of ERK1/2 signaling are of major therapeutic interest, since permanent activation and inactivation of this cascade both appear detrimental. Novel ERK1/2 targeting strategies should increase the therapeutic efficacy by circumventing drug-resistance and reduce cardiac side-effects that currently limit their application 2,4,[56][57][58] . In this regard, interference with ERK dimerization holds promise, since AKT activation as one compensatory mechanism that contributes to drugresistance was prevented in HT29 cells, and most importantly no side-effects were detectable in the AAV9-EDI model nor for the overexpression of monomeric ERK2 ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…(v) Identifying drug targets. Gronich et al [ 86 ] evaluated the association between tyrosine kinase-targeting drugs and the risk of new-onset heart failure, using nested case-control analysis. (vi) Clinical supplementary diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In species cross activity analysis, heart endocardium, lung type II alveolar epithelial cell and surrounding vessels showed moderate positive staining of EGFR expression, but not in cardiac muscle fibers, indicating potential crossing binding APZ001 or anti-EGFR mAb drugs on heart endocardium cells and lung epithelial cells. Heart side-effects caused by Erbitux were reported [10][11][12] recently. They reported that patients might suffer from heart rate increase, sense of suppression in the chest, breathe hard and fatigue susceptibility, and even heart failure 10 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Heart side-effects caused by Erbitux were reported [10][11][12] recently. They reported that patients might suffer from heart rate increase, sense of suppression in the chest, breathe hard and fatigue susceptibility, and even heart failure 10 . Overbeek et al 11 reported that Erbitux exposure was 1.72 fold OR (1.10-2.69) associated with increased heart failure risk.…”
Section: ■ Discussionmentioning
confidence: 99%